Molecular docking studies of an isolated angucycline of Stereospermum fimbriatum, a novel anti-MRSA agent - Fadhlina, Anis; Sheikh Mohamed, Hassan Ibrahim; Lestari, Widya (Penerbit UTM Press, Universiti Teknologi Malaysia, 2023)
A novel angucycline, C1 isolated from Stereospermum fimbriatum stem bark was subjected to molecular docking studies on five main targets of penicillin-binding protein 2a (PBP2a), β-lactamase, DNA topoisomerase IV, dehydrosqualene synthase (CrtM) and sortase A (SrtA) for anti-MRSA activity. The binding sites and docking scores of known inhibitors (positive control) were compared with C1. Docking analysis was carried out by AutoDock 4.0 package. The binding site of C1 closely resembled the positive control in all screened receptors. Inhibition constant of C1 was lower than the positive control tested for PBP2a, β-lactamase, dehydrosqualene synthase and sortase A except against DNA Topoisomerase IV. Structure-activity relationship (SAR) analysis of C1 showed that 7-CO was the most significant contributor to its activity since it formed hydrogen bonds with four of the five screened receptors. Molecular docking of C1 indicated that C1 can be a good candidate for new anti-MRSA drug development.